Brucellosis and toxoplasmosis in pregnancy - Perez, Manuel (2015)
Brucellosis (Malta fever, undulant fever, Disease Bag) .- Today it is recognized that both the melitenses micrococcus (D. Bruce) as abortion bacillus (Bang), are related germs, differing only varieties: goat (melitenses Brucella), bovine (Brucella abortus) and swine (Brucella suis), which differ in their immune characters and culture.